Respuesta :

Problem 1

Answer:  Choice B) x = -2

------------------

Explanation:

Add the equations straight down.

The x terms add to 5x+(-3x) = 2x

The y terms cancel out since 3y+(-3y) = 0y = 0

The right hand sides add to -7+3 = -3

After adding the equations you should get 2x = -4 which solves to x = -2

=====================================================

Problem 2

Answer:  y = 4

------------------

Explanation:

Since 5x = 0, this means x = 0 after dividing both sides by 5.

Use this to find y

y = -4x+4

y = -4(0)+4

y = 4

If you want the value of z, then

x = -3y+z+6

0 = -3(4)+z+6

0 = z-6

6 = z

z = 6